2013
DOI: 10.1080/10572252.2013.775628
|View full text |Cite
|
Sign up to set email alerts
|

The Usability of Print and Online Video Instructions

Abstract: This study investigates the usability of print and online video instructions for computer tasks. Usability tests, comprehension tests, and questionnaires were collected from participants, and 4 areas of usability were analyzed: effectiveness, retention, satisfaction, and preference. Findings show marginal differences between the 2 mediums, except in terms of user satisfaction and instruction length. This research helps technical communicators better understand the affordances, or potentials and limitations, of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 49 publications
0
34
1
Order By: Relevance
“…A study by Payne, Chesworth, and Hill () compared four conditions (paper‐based tutorial, video tutorial, paper plus video and no instructions) on procedural knowledge development for McDraw and found a time advantage for the paper‐based tutorial. A study by Alexander () compared the use of a paper‐based tutorial or video tutorial for the creation of a table of contents and the use of mail merge in Microsoft Word and showed no specific benefits of either tutorial. Research by Palmiter, Elkerton, and Baggett () and Palmiter and Elkerton () showed better results during training for video instructions, but better test results for written instructions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Payne, Chesworth, and Hill () compared four conditions (paper‐based tutorial, video tutorial, paper plus video and no instructions) on procedural knowledge development for McDraw and found a time advantage for the paper‐based tutorial. A study by Alexander () compared the use of a paper‐based tutorial or video tutorial for the creation of a table of contents and the use of mail merge in Microsoft Word and showed no specific benefits of either tutorial. Research by Palmiter, Elkerton, and Baggett () and Palmiter and Elkerton () showed better results during training for video instructions, but better test results for written instructions.…”
Section: Introductionmentioning
confidence: 99%
“…In short, the paper‐based tutorial is equipped with structural overviews that enhance the accessibility of its content. For video, the accessibility of content can form an important obstacle (e.g., Alexander, ; Palaigeorgiou & Despotakis, ).…”
Section: Introductionmentioning
confidence: 99%
“…While Mestre (2012) reported an advantage of paperbased instructions, Alexander (2013) found no differences. Three other studies found the video tutorial significantly more successful than the paper-based version (Lloyd and Robertson 2012;van der Meij 2014, 2015).…”
Section: Introductionmentioning
confidence: 64%
“…On top of that, a study by Palmiter [23] came to the conclusion that both text tutorials and video tutorials have their specific benefits. And there are even studies that could not find significant differences between text and video tutorials at all (e. g. [24,3,6]). …”
Section: Related Studiesmentioning
confidence: 99%
“…For video tutorials Alexander reported that learners watch the whole video(s) (which is time consuming) [3] instead of picking particular scenes. However, studies by Mestre and Alexander both confirm that learners have trouble finding specific scenes after watching a video [21,3]. As an advantage of video tutorials, participants in a study by deVaney perceived them as "more human" [6].…”
Section: Related Studiesmentioning
confidence: 99%